Globalização em paisagens linguísticas e usos de marcadores discursivos: policentricidade, escalas e metapragmática nas práticas linguísticas de jovens urbanos e quilombolas - Batista, Thaís Elizabeth Pereira (2015)
This work is a sociolinguistic research, from the view of the interaction, of the uses of discourse markers by young in two different contexts in the state of Goiás, with the effects of globalization as background (BLOMMAERT, 2010) on supposed differences between the groups. A group of young people is from a urban area of medium sized, the city of Anápolis - GO. The other group of young people is from a quilombo area (remnants of resistant slaves) in a rural area, but with many globalization indexes, including eco-tourism and heritage tourism (HELLER, 2010; JAFFE, 2011). Both contexts are located in area of cerrado biome in the Midwest of Brazil. The scope of this study is discuss how globalization indexes interpose on the linguistic landscapes (BLOMMAERT, 2014), in other words in written and semiotized materials availables in public spaces and how those aspects can affect the interaction. The concern in investigating a field in a urban area and the other in a rural area comes from statements that the sociolinguistic theories of variationist orientation, very propagate in Brazil, make about the differences of language characteristics of the spaces based on this dichotomy. However, the fields selected for the analysis show that the language practices of young may converge in many ways which enabled analysis of linguistic uses based on differences and similarities in interactional patterns. This analysis provides a way of handling fields that considers the differences, but finding points of similarity in the continuous between the two fields. For such research were adopted theoretical tools intrinsic interactional sociolinguistics, based on studies from the perspective of sociolinguistic research in complex contexts, or mobility sociolinguistic (BLOMMAERT, 2010) considering how global elements as complex forms of migration and dissemination of information at high speed through the Internet, for example (BLOMMAERT, 2010; JACQUEMET, 2005) have importance in linguistic practices of the people, enabling those practices great complexity and unpredictability. Concepts such as scales, polycentricity (BLOMMAERT, 2010) and metapragmatics (SILVERSTEIN, 1993) will be used as theoretical tools for the joint analysis of the data generated through images, linguistic landscapes, and the data recorded on audio of everyday interaction (RAMPTON, 2003).